CYBERSPACE REGULATION: CESURISTS AND TRADITIONALISTS - Lino Santos (JANUS.NET, e-journal of International Relations, 2015)
In the amazing Code and Other Laws of Cyberspace , Professor L. Lessig writes "that something fundamental has changed" with cyberspace with regard to the state's ability to enforce the law. On the one hand, the structure and characteristics of cyberspace pose some difficulties related to jurisdiction and the choice of applicable law. On the other, it raises questions about the very concept of sovereignty as we know it. This paper examines the arguments of those who advocate a regulation of cyberspace on the edges of state sovere ignty or within a new concept of sovereignty and capacity to enforce the law, and the arguments of those who reject this exceptional treatment of cyberspace. .